2021
DOI: 10.1073/pnas.2110298118
|View full text |Cite
|
Sign up to set email alerts
|

The citron homology domain as a scaffold for Rho1 signaling

Abstract: Aspergillus fumigatus is a human opportunistic pathogen showing emerging resistance against a limited repertoire of antifungal agents available. The GTPase Rho1 has been identified as an important regulator of the cell wall integrity signaling pathway that regulates the composition of the cell wall, a structure that is unique to fungi and serves as a target for antifungal compounds. Rom2, the guanine nucleotide exchange factor to Rho1, contains a C-terminal citron homology (CNH) domain of unknown function that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 75 publications
(132 reference statements)
0
8
0
Order By: Relevance
“…Dityrosine transporter 1 plays an essential role in spore wall maturation in Saccharomyces cerevisiae . Rho1 has been identified as an important regulator of the signaling pathway that regulated the compositions of the cell wall . All of these results clearly indicated that the cell wall of U.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Dityrosine transporter 1 plays an essential role in spore wall maturation in Saccharomyces cerevisiae . Rho1 has been identified as an important regulator of the signaling pathway that regulated the compositions of the cell wall . All of these results clearly indicated that the cell wall of U.…”
Section: Resultsmentioning
confidence: 93%
“…44 Rho1 has been identified as an important regulator of the signaling pathway that regulated the compositions of the cell wall. 45 All of these results clearly indicated that the cell wall of U. virens underwent inhibition by 2,4-DTBP.…”
Section: ■ Materials and Methodsmentioning
confidence: 87%
“…Our structural modeling showed that mNRK and cNRK CNH domains form a b-propeller structure similar to the prototypical CNH domain of yeast Rom2 (30). The mNRK CNH domain has evolved to acquire complete polybasic clusters and a larger positively charged surface in contact with the lipid bilayer.…”
Section: Molecular Evolution and Structure Of The Nrk Cnh Domainmentioning
confidence: 80%
“…The PH domain is distinguished from homologous PH domains by a loop insertion between strands β6 and β7 that packs against the CNH domain (Supplementary Figure S2B). The CNH domain forms a 7-bladed beta propeller with strongest homology to the CNH domain of yeast Rho1 (35). The CNH domain is held together by a beta strand contributed by the linker between the PH domain and blade 1 of the beta propeller (Figure 2B, yellow) and the C-terminus of the construct (Figure 2A, dark brown) which together form blade 7.…”
Section: Resultsmentioning
confidence: 99%